Utilization of Fobio and Streptomyces sp. in Improving the Growth of Shallots - Sri Wiyatiningsih; Penta Suryaminarsih; Gusdino Hasyidan (Nusantara Science and Technology Proceedings, 2021)
Shallots (Allium ascalonicum L.) is a spice vegetable commodity that is needed by the community as a cooking spice to increase the taste of eating pleasure and for traditional medicines that are efficacious for health. Control using chemicals is believed to be effective in overcoming pathogen attacks, but the continuous addition of chemical pesticides will have a negative impact on the environment and consumers. To deal with the negative impact of the use of these chemicals, namely by applying a sustainable farming system that was originally a conventional farming system and includes organic agriculture (Fobio biopesticide application) and biological (Application of Streptomyces sp. biological agents). The purpose of this study was to determine the effectiveness of the formulation of the biopesticide Fobio and the biological agent Streptomyces sp. to increase the growth of leeks and minimize the negative impact of using fungicides in Bulugunung Village, Plaosan District, Magetan Regency but still have the potential for maximum harvest success. The study was conducted from March to May 2021. This study used a Completely Randomized Design (CRD) consisting of 4 treatments with 6 replications. Each experimental unit consisted of 100 plants. Observation parameters consisted of leaf height and number of leaves of shallot plants. The results showed that the application of biopesticide Fobio and biological agents Streptomyces sp. did not significantly affect the height of the shallot plant and had a significant effect on the number of leaves of the shallot plant